Multi-agent oriented programming with JaCaMo - Boissier, Olivier; Bordini, Rafael H.; Hübner, Jomi F.; Ricci, Alessandro; Santi, Andrea (Science of computer programming, 2013)
This paper brings together agent oriented programming, organisation oriented programming and environment oriented programming, all of which are programming paradigms that emerged out of research in the area of multi-agent systems. In putting together a programming model and concrete platform called JaCaMo which integrates important results and technologies in all those research directions, we show in this paper, with the combined paradigm, that we prefer to call “multi-agent oriented programming”, the full potential of multi-agent systems as a programming paradigm. JaCaMo builds upon three existing platforms: Jason for programming autonomous agents, Moise for programming agent organisations, and CArtAgO for programming shared environments. This paper also includes a simple example that illustrates the approach and discusses some real-world applications that have been or are being developed with JaCaMo. ► This paper unravels a fully fledged “multi-agent oriented programming” paradigm. ► It brings together agent/organisation/environment oriented programming. ► We discuss a concrete platform for programming multi-agent systems called JaCaMo. ► The paper also includes a simple example that illustrates the approach. ► Some applications being developed with JaCaMo are also briefly presented.